2006
DOI: 10.1007/s10582-006-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of time dependent plasma plume induced during laser welding

Abstract: Theoretical modelling of the plasma plume induced during welding of iron sheets with CO 2 laser are presented. The set of equations consists of equation of conservation of mass, energy, momentum and the diffusion equation and is solved with the use of commercially available program Fluent 6.1. The computations are made for the laser power of 1 700 W and shielding gas argon. Two solutions are taken into account stationary and non-stationary. The results show significant difference between these two cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This further leads to generating a keyhole and would then lead to some degree of melting, material removal through vaporisation. During this instance, the vaporised substance mixes with the assist gas to form a plasma plume as mentioned by Hoffman et al [35], Raciukaitis et al [36] and Boulmer et al [37]. As the plasma plume comprises of the gas mixture, the main source of C induction occurs from the assist gas molecules [38].…”
Section: Influence Of Assist Gasesmentioning
confidence: 95%
“…This further leads to generating a keyhole and would then lead to some degree of melting, material removal through vaporisation. During this instance, the vaporised substance mixes with the assist gas to form a plasma plume as mentioned by Hoffman et al [35], Raciukaitis et al [36] and Boulmer et al [37]. As the plasma plume comprises of the gas mixture, the main source of C induction occurs from the assist gas molecules [38].…”
Section: Influence Of Assist Gasesmentioning
confidence: 95%
“…Time-dependent measurements of the parameters of the plasma plume under welding conditions are scarce. The preliminary results of time-dependent spectroscopic measurements were shown in [9]. It has been found that the composition of the plasma plume changed and depended on the strength of the vapour bursts.…”
Section: Introductionmentioning
confidence: 99%
“…The vapourisation of the melt pool not only has detrimental effects on the physical properties of the part, but the resulting plasma/metal vapour plume can cause a number of issues. It can interact directly with the laser, causing damping and scattering of the beam, [126]- [128]. The nanoscale condensate that forms after the plume cools down is mostly removed from the powder bed by high velocity shielding gas.…”
Section: Keyholingmentioning
confidence: 99%